Народна архітектура та житло українців-слобожан - Сушко, В. (Матеріали до української етнології, 2024)
Житло є чи не найважливішим складником будь-якої етнічної культури. На формуванні народної архітектури українців Слобожанщини позначився масовий переселенський рух XVII ст. з Карпатського регіону, Галичини, Поділля, Волині, Правобережного Полісся та Середньої Наддніпрянщини. На планувальні принципи й будівельні матеріали впливали як природні умови, так і соціально-економічні зміни: у козацькі часи хати будували з дубових колод, вони мали підлогу, вкривали їх ґонтом; епоха закріпачення (імперського та радянського), війни спричинили перехід до покриття хат очеретом і соломою, заміну підлоги глиняною долівкою, застосування доступніших матеріалів для зведення стін (дешевша деревина, глина, глинобитна цегла), спрощення номенклатури меблів. Покращення соціально-економічних умов приводило до урізноманітнення будівельних практик. На основі зібраних польових етнографічних записів можна говорити про зміну планувальних принципів житла від трикамерної «хати на дві половини» до житла, внутрішній простір якого ділився піччю, а до фасадної стіни доєднувалися господарські приміщення, сіни та веранда, що було характерно в першій половині ХХ ст., і вже до зовсім сучасного «котеджного» житла з помешканням-«студією» або, навпаки, дуже ускладненого внутрішнього хатнього простору. Матеріалом для написання представленої розвідки стала фіксація явищ сільського життя, а також міські реалії – і то не лише районних центрів, наприклад Вовчанська, Куп’янська та інших міст Харківщини, Охтирки чи Тростянця на Сумщині й самих Сум, а й міста-мільйонника Харкова, де донині є райони «приватного сектора» – сільської забудови. Dwelling is perhaps the most important component of any ethnic culture. The mass resettlement movement of the 17th century from the Carpathian region, Halychyna, Podillia, Volhynia, the Right-Bank Polissia, and the Middle Over Dnipro Lands has influenced the formation of the folk architecture of Ukrainians in Slobozhanshchyna. Planning principles and building materials are affected by both natural conditions and socioeconomic changes: in Cossack times huts have been built out of oak logs, had a floor, and were covered with shingles; the epoch of serfdom (imperial and Soviet), wars led to the transition to covering huts with reeds and straw, replacing the floor with a clay floor, using more affordable materials for building walls (cheaper wood, clay, adobe bricks), and an extreme simplification of the furniture nomenclature. The improvement of socio-economic conditions has led to the diversification of construction practices. Based on the collected field ethnographic materials, it can be stated that the planning principles of housing have been changed from a three-chamber «house in two halves» to housing, the internal space of which is divided by a stove, and utility rooms, a porch, and a veranda are attached to the facade wall. This phenomenon is typical of the first half of the 20th century. The process of transformation is finished by a completely modern «cottage» housing with a «studio» apartment, or vice versa, a very complicated internal house space. The submitted study is written after the recording of the phenomena of rural life as well as the urban realities – and not only district centers, for example, Vovchansk, Kupiansk and other cities of the Kharkiv region, Okhtyrka or Trostianets in the Sumy region and Sumy itself, but also the city with a population of over a million Kharkiv, where there are still areas of the «private sector» – rural buildings.